STUDI EMPIRIS TENTANG PENGARUH PENGETAHUAN PAJAK, KESADARAN WAJIB PAJAK DALAM MEMBAYAR PAJAK, DAN PERSEPSI TERHADAP KEPATUHAN WAJIB PAJAK DI KAB. TEGAL (Students' Journal of Accounting and Banking, 2012)
The purpose of this study was to determine and analyze the effect of tax knowledge, awareness of taxpayer in paying taxes and the perception of taxpayer compliance.The population in this study is that there are corporate taxpayers in the district of Tegal. Based on data from the Tax Office Primary Tegal registered and still be effective. The sampling technique used in this study is to use non probability sampling.Based on the results of hypothesis testing can be concluded that: There are positive and significant correlation between knowledge of the taxpayer (X1) of taxpayer compliance (Y), There is a positive influence and no significant relationship between awareness of paying taxes (X2) on taxpayer compliance (Y); There are positive and significant influence between perceptions of the tax man (X3) of taxpayer compliance (Y); as well There are positive and not significant between the perception of compliant taxpayers criteria (X4) of taxpayer compliance(Y).Keywords: Compliance taxpayers, tax officers perception, perception